Maternal and paternal parenting styles as a whole: validation of the simple form of the Parenting Style Evaluation Scale - Balaguer, Álvaro; Benitez, Edgar; De la Fuente, Jesus; Osorio, Alfonso (Anales de Psicología / Annals of Psychology, 2021)
Oliva’s Escala para la Evaluación del Estilo Parental (EEEP) [Scale for the evaluation of parenting styles] asks adolescents about their parents’ education styles separately (“your father” and “your mother”) or in a combined way (“your parents”), but only the separated version has been tested for validity. The objective of this work was to carry out a validation of the combined version. A sample of 1507 adolescents, aged 12 to 18 years, was recruited. Exploratory and confirmatory factor analyses were run in two independent subsamples. Then, structural equation models (SEM) were run in order to test the association between the EEEP’s subscales and adolescent outcomes (optimism, pessimism, and academic achievement). Results showed a good fit of the instruments’ structure. Furthermore, the subscales showed associations with the outcomes. The EEEP can be reliably used in its combined form, which results in a reduction of items, often beneficial for research.